An Analysis of the Changes in British Workers' Real Wages since the 19th Century - John H. Pencavel (Institute of Labor Economics (IZA), 2024)
The increase in the real wages of British workers over the last one hundred years is often attributed to the growth in labour productivity, but this has rarely been confirmed. In the research reported here, this ascription is confronted with annual observations on wages and productivity spanning more than a century. A positive wage-productivity link is, indeed, found. However, productivity growth alone removes little of the variation over time in real wage changes. When trade union membership was rising, unions were able to direct increases in incomes to the earnings of rank-and-file workers.
Keywords: J31; J42; N14; N34; 330; real wages; labour productivity; trade unions; monopsony